FOTOTERAPI BUKAN ALASAN UNTUK GAGAL ASI EKSKLUSIF - Suwarniningsih; Nursanti, Ida (Jurnal Media Ilmu Kesehatan, 2013)
Background : Exclusive breastfeeding is recommended based on the evidence of the benefits and proper nutrients for the baby. Phototherapy is done for the treatment of hyperbilirubinemia in infants with several side effects such as: increased temperature, increased insensible water loss, and a separate room will increase a risk fordisanting exclusive breastfeeding. Objective : This study aimed for identifying the correlation between phototherapy and continuity of exclusive breastfeeding at Perinatology room of Wates Hospital Propinsi Daerah Istimewa Yogyakarta 2012. Method : This was a prospective cohort study that was conducted from 1st December until 31 December 2012. Sixty eight hospitalized babies at a neonatology ward were involved in this study. Using a purposive sampling method, 34 babies receiving photothetapy were assigned into the treatment group and 34 babies were assigned into control group. The breastfeeding continuity was measured using a valid and reliable observational checklist which was constructed by the researcher. Result : There was no correlation between phototherapy with continuation of exclusive breastfeeding (p = 0.27) Conclusion and suggestion : Phototherapy treatment did not interrupt continuityof breastfeeding. Based on this study, we strongly recommend that during the phototherapy treatment affecting on separation between mothers and baby, the breastfeeding continuity needs to be concerned. Keywords : Exclusive breastfeeding, phototherapy.